The librarianist : a novel - deWitt, Patrick, 1975- (Ecco, 2023)
"Bob Comet is a retired librarian, isolated but not lonely, living out his quiet days in a mint-colored house in Oregon, surrounded by his books and small comforts. One morning, out on his daily walk, he performs an act of kindness that brings him into contact with a nearby senior center, where he soon begins volunteering. Here, as a community of peers and friends gathers around Bob, and following a happenstance brush with a painful complication from his past, the events of his life and the details of his character are revealed. Behind Bob Comet's plain facade is the story of an unhappy child's runaway adventure, of true love found and stolen away, of the purpose and pride found in vocation, and the ultimate acceptance of a life lived to the side of the masses. The Librarianist is a wide-ranging and ambitious homage to the life lived through and for literature. With his inimitable verve, skewed humor, and compassion for the outcast, deWitt celebrates the extraordinary in the so-called ordinary life, and depicts beautifully the turbulence that sometimes exists beneath a surface of serenity"--